A New Object of Translation Studies: The Lithuanian Eurolect - Pekūnas, Žygimantas (Vertimo studijos, 2024)
This article aims to introduce readers to the Lithuanian Eurolect and stimulate research on this underexplored topic. It provides a brief overview of Eurolects—i.e., Europeanized variants of EU official languages shaped by translation and language contact. The article reviews existing studies on Eurolects and explores the hypothetical Lithuanian Eurolect. It outlines systematic approaches to studying this phenomenon with the aid of corpora and suggests potential research avenues, including lexical, grammatical, and discourse features of Eurolects.